2007
DOI: 10.1074/jbc.m609355200
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis for Ligand Specificity in a Mouse Olfactory Receptor

Abstract: Sequence differences between members of the mouse olfactory receptor MOR42 subfamily (MOR42-3 and MOR42-1) are likely to be the basis for variation in ligand binding preference among these receptors. We investigated the specificity of MOR42-3 for a variety of dicarboxylic acids. We used site-directed mutagenesis, guided by homology modeling and ligand docking studies, to locate functionally important residues. Receptors were expressed in Xenopus oocytes and assayed using high throughput electrophysiology. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
103
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 48 publications
11
103
0
Order By: Relevance
“…Amino acid substitutions in vertebrate chemosensory receptors can result in changes in ligandbinding affinity and confer differences in odorant sensitivity (Krautwurst et al 1998;Feinstein and Mombaerts 2004;Reed et al 2004;Nie et al 2005;Abaffy et al 2007;Keller et al 2007). Thus, it is of particular interest that Or43a harbors an isoleucine to methionine substitution that contributes to variation in responsiveness to benzaldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid substitutions in vertebrate chemosensory receptors can result in changes in ligandbinding affinity and confer differences in odorant sensitivity (Krautwurst et al 1998;Feinstein and Mombaerts 2004;Reed et al 2004;Nie et al 2005;Abaffy et al 2007;Keller et al 2007). Thus, it is of particular interest that Or43a harbors an isoleucine to methionine substitution that contributes to variation in responsiveness to benzaldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…Azelaic acid (AzA) and suberic acid are known Olfr544 ligands (10,11). We examined the effect of Olfr544 in Hana3A cells transfected with N-terminal Lucy-FLAG-tagged Olfr544.…”
Section: Activation Of Olfr544 By Azelaic Acid Stimulates Camp Responmentioning
confidence: 99%
“…For ORs, this point might not be too critical, since odorants are usually low-molecular-weight organic compounds and therefore relatively small compared to the ligands of other GPCRs. A number of OR models in which odorants were docked and which were tested by sitedirected mutations have revealed that odorants dock deep into the pocket (Abaffy et al 2007;Katada et al 2005;Launay et al 2012) and do not interact with ECL2.…”
Section: Application To Structure Modeling and Virtual Screening Of Orsmentioning
confidence: 99%
“…Using site-directed mutagenesis and functional expression the authors show that the orientation of odorants within a homo logy modelingderived binding pocket of olfactory receptor orthologs is defined by evolutionary conserved amino acid positions. mOR42-3, mOR42-1 2.8 Å bovine rhodopsin 3D structure Abaffy et al 2007 Investigation of the specificity of mOR42-3 for dicarboxylic acids. Use of site-directed mutagenesis to locate functionally important residues.…”
Section: Application To Structure Modeling and Virtual Screening Of Orsmentioning
confidence: 99%